Peran Keluarga dalam Prevensi Penyalagunaan Napza - Tina Afiatin (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2005)
The article tries to examine the important role of family in the preventions of drugs abuse. Drug abuse prevention may be carried out at two levels: individual and family. This article focused on the role of family as a system that maintain yhe life balance (homeostatic) among its individual members. It also serves as the basis which can increase or decrease the prevalence of its members to be engaged in drug abuse. Ways on how the family can actively participate drugs abuse prevention is discussed.Keyword: family role.